Custom-made 3D-printed cup-cage implants for complex acetabular revisions: evaluation of pre-planned versus achieved positioning and 1-year migration data in 10 patients - Zampelis, Vasileios; Flivik, Gunnar (Acta Orthopaedica, 2020)
Background and purpose — The use of custom-made 3D-printed titanium implants for the reconstruction of large acetabular defects has been successively introduced in the last decade. In an observational cohort study we evaluated the agreement between preoperatively planned and actually achieved cup-cage position as well as 1-year follow-up migration of the cup-cage component. Patients and methods — 10 patients with Paprosky III defects underwent revision surgery using a custom-made 3D-printed cup-cage. The position of the implant on postoperative CT scan was compared with the preoperative plan and the postoperative CT scan was compared with the 1-year follow-up CT scan. Results — There was a median deviation in postoperative position versus planned in inclination of 3.6° (IQR 1.0–5.4), in anteversion of –2.8° (IQR –7.5 to 1.2), and in rotation of –1.2° (IQR –3.3 to 0.0). The median deviation in position of the center of rotation (COR) was –0.5 mm (IQR 2.9 to 0.7) in the anteroposterior (AP) plane, –0.6 mm (IQR –1.8 to –0.1) in the mediolateral (ML) plane, and 1.1 mm (IQR –1.6 to 2.8) in the superoinferior (SI) plane. The migration between postoperative and 1-year follow-up caused a mean change in inclination of 0.04° (IQR –0.06 to 0.09), in anteversion of –0.13° (IQR –0.23 to –0.06), and in rotation of 0.05° (IQR –0.46 to 1.4). The migration of COR was –0.08 mm (IQR –0.18 to –0.04) in the AP plane, 0.14 mm (IQR –0.08 to 0.22) in the ML plane, and 0.06 mm (IQR –0.02 to 0.35) in the SI plane. There was no re-revision. Interpretation — The early results show good agreement between planned and achieved cup-cage position and small measured migration values of the cup-cage component at the 1-year follow-up.